PERSEPSI MAHASISWA FAKULTAS KEPERAWATAN UNIVERSITAS RIAU MENGENAI METODE PEMBELAJARAN PROBLEM BASED LEARNING (PBL), - Riskhita Mutiara Salshabil (Jurnal Medika Hutama, 2022)
Aim: To explore Nursing Faculty Stundents’ perspective toward the PBL learning method. Methods: The study applied descriptive design. The respondents consisted of 414 nursing students select using total sampling technique. The data was gathered using questionnaire was adopted from the Course Experience Quesionnaire (CEQ) and modified by researches and has been tested for validity and reliability. Results: the results showed that 220 respondents (53.1%) had positive perspective on the PBL method and 114 respondents (46.9%) had negative perceptions. On sub-variabels of facilities and infrastructure and tutor and lectures’ roles, the majority of student still have negative perceptions (44.7%) and (40.1%) because there are still things that are not running optimally from the 8 domains that researches listed in this study. Conclusion: Students' perceptions of the PBL method in the Faculty of Nursing, University of Riau generally show a positive perception. It is suggested that the institution be able to complete the infrastructure to support the learning process and optimize the tutor's role in the implementation of the tutorial so that the implementation of PBL can be considered running optimally.